Procedimentos de intervenção para corrigir um déficit no controle de estímulos: uma revisão de estudos empíricos - Corato, Luciana Lorenzi (2013)
A deficit in stimulus control that has been called overselectivity / restricted control / selective control occurs when only a limited number of environmental stimuli comes to control behavior at the expense of other aspects of the environment. This deficit has a high level of occurrence in people with atypical development, particularly in those with autism spectrum disorders, but it is not restricted to this population. The objective of this study was to review the experiments developed to evaluate procedures aimed to correct this deficit. A search was conducted on four databases, both in English and Portuguese, with the following keywords: restricted control, selective control and overselectivity. Eleven papers encompassing 16 experiments were found; the majority (13) conducted with people with atypical development, and the remaining with participants with typical development at different ages. Nine procedures have been identified employing tasks such as SMTS, DMTS, discrimination between two stimuli simultaneously presented, observing response procedures, differential observation response (DOR), compound DOR, overtraining, manipulation of the stimuli s characteristics, functional object-use and their graphic representations or photographs and fading. The stimuli presented during the discrimination tasks could be symbols, graphic representations, abstract figures, geometric shapes, words, photographs, drawings and concrete objects. Several experimental designs were employed to evaluate the effect of the intervention on the deficit in stimulus control, the majority (13 experiments) with repeated measures and the remaining comparing independent groups plus intra-subject designs. Various measures to evaluate stimulus control were employed and variable results were obtained. In almost all studies the procedures were able to reduce the deficit in stimulus control, although not totally. In some studies discriminative performance improved only when the procedure was in effect, but returned to baseline levels after its withdrawal